The Influence of WCTO, TATO and SG on ROA at PT Kalbe Farma Tbk - Febriana, Yola; Priyanto, Aria Aji (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to determine the effect of Working Capital Turnover, Total Asset Turnover, and Sales Growth on Return on Assets (ROA) at PT Kalbe Farma Tbk. Using Quantitative Methods. Sample Financial Report of PT Kalbe Farma Tbk. for 10 years. Data analysis uses descriptive statistical tests, classical assumption tests, multiple regression analysis, hypothesis testing and coefficient of determination tests. The partial test results of Working Capital Turnover do not have a significant effect on Return on Assets. Total Asset Turnover has a significant effect on Return on Assets. Sales Growth has no effect on Return on Assets. The results of simultaneous testing of Working Capital Turnover, Total Asset Turnover, and Sales Growth have a significant effect on Return on Assets. The results of the Coefficient of Determination test show that Adjust R Square is 0.949. Working Capital Turnover, Total Asset Turnover, and Sales Growth on Return on Assets have a contribution of 94 .9%, Meanwhile 5.1% was influenced by other variables not analyzed in this study.